The “Austrian School of Critical Political Economy”? A Review of Thomas Allmer’s Book “Towards a Critical Theory of Surveillance in Informational Capitalism” - Jernej Amon Prodnik (tripleC: Communication, Capitalism & Critique)
This article is a review of Thomas Allmer’s book “Towards a Critical Theory of Surveillance in Informational Capitalism”. The book was published in 2012 by the publishing house Peter Lang (in Frankfurt am Main, Berlin, New York, Oxford […]). In the start of the article the author also poses the question whether there is a new school of thought emerging, namely the “Austrian School of Critical Political Economy”.